Peran Customer Satisfaction Memediasi Pengaruh Brand Image dan Perceived Value Terhadap Repurchase Intention Iphone Pada Generasi Z Di Kabupaten Kudus - Khoirunnisa, Putri Salsa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Achmad Yani Yogyakarta, 2024)
This study aims to examine the influencing factors of Repurchase Intention on Iphone with Generation Z users in Kudus Regency. The determining factors considered are Brand Image and Perceived Value which are reinforced by the Customer Satisfaction variable. This study used quantitative research methods with non-probability sample (purposive sampling) technique that is by distributing digital questionnaires with respondents having certain categories, namely Generation Z in Kudus Regency who have purchased Iphone as much as 100 respondents. This research uses structural model analysis techniques using the Smart-PLS version 3 test tool. The results of data analysis show that Brand Image has a significant effect on Repurchase Intention, Perceived Value has a significant effect on Repurchase Intention, Customer Satisfaction has a significant effect on Repurchase Intention, Customer Satisfaction is able to mediate the influence between Brand Image and Repurchase Intention, and Customer Satisfaction is also able to mediate the influence between Perceived Value and Repurchase Intention. Thus, these findings contribute to Smartphone companies, especially Iphone.